Accuracy of Using English Collocation in Writing Descriptive Texts at SMK Cahaya Harapan Students - Magpika Handayani; Yovita Angelina (STKIP Singkawang, 2020)
The purpose of this study is to know the accuracy of using English collocation in writing descriptive text. The use of collocation in writing is one of the important things in creating a paper. The correct use of collocation is often a problem in writing. Students often do not use accurate collocation due to differences in collocations held in the first language with collocations in English. The ability to write using accurate collocation might have an impact on the comfort of the reader in understanding the meaning of the writing written. The method used in this research is a descriptive method by describing students' collocation accuracy that is gathered from task and students descriptive writing. Students do not know at all about collocation and the collocation used is Indonesian translated. Descriptive writing of SMK Harapan Harapan students specifically the marketing department that uses collocation is still not coherent, not developed and there are still many errors. Based on the results of the research, the writer found that students understand how to write descriptive text, but they do not understand how to express factual description in their writing with collocation accurately because they are not familiar with the collocation that should be used in English as the target language.